ANALYSIS OF FINANCIAL SHENANIGANS IN PT PERTAMINA PATRA NIAGA'S FINANCIAL REPORT - Ninuk Riesmiyantiningtias,; Rizky Amalia,; Amalia Tresna Fadhilah, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study aims to analyze the financial statements of PT Pertamina Patra Niaga using Common Size Analysis which compares components in the company's financial statements and concludes with the detection that is common in shenanigans. The analysis of the case study of oil and refinery product governance irregularities involving PT Pertamina Patra Niaga was carried out by analyzing in depth the data in the financial statements. The type of research conducted is descriptive with a case study method using a combination of quantitative and qualitative statistical research techniques. The research data obtained is secondary data in the form of financial statements of PT Pertamina Patra Niaga for the period of 2020 – 2023. The results of the study show that there is no significant early detection of financial shenanigans. The company's financial performance is quite good, especially in terms of profitability and liquidity despite fluctuations